Correlations to predict thermal performance affected by working fluid's properties of vertical and horizontal closed-loop pulsating heat pipe - Sakulchangsatjatai P. (2017)
Objectives of this paper are to investigate the effects of dimensionless numbers on the thermal performance, and to establish correlations to predict the thermal performance of the vertical and a horizontal closed-loop pulsating heat pipe. The heat pipes were made of long copper capillary tubes with 26 meandering turns and both the ends were connected together to form a loop. R123, R141b, acetone, ethanol, and water were chosen as variable working fluids with a constant filling ratio of 50% by total volume. The inlet temperature of the heating medium and the adiabatic section temperature were constantly controlled and maintained at 80 °C and 50 °C, respectively. The thermal performance was represented in terms of the Kutateladze number. It can be concluded that when the Prandtl number of the liquid working fluid, as well as the Karman number, increases, the thermal performance increases. On the other hand, when the Bond number, the Jacob number, and the Aspect ratio increase, the thermal performance decreases. These effects of the dimensionless numbers on the thermal performance are valid for both the heat pipes, except in the case of Bond number which has no effect on the thermal performance as far as the horizontal heat pipe is concerned. Moreover, correlations to predict thermal performance have been successfully established.